High precision tracking analysis of cell position and motion fields using 3D U-net network models. (March 2023) - Yuan, Li-Xin; Xu, Hong-Mei; Zhang, Zi-Yu; Liu, Xu-Wei; Li, Jing-Xin; Wang, Jia-He; Cui, Hao-Bo; Huang, Hao-Ran; Zheng, Yue; Ma, Da
Abstract: Cells are the basic units of biological organization, and the quantitative analysis of cellular states is an important topic in medicine and is valuable in revealing the complex mechanisms of microscopic world organisms. In order to better understand cell cycle changes as well as drug actions, we need to track cell migration and division. In this paper, we propose a novel engineering model for tracking cells using cell position and motion fields (CPMF). The training sample does not need to be manually annotated, and we modify and edit it against the ground truth using auxiliary tools. The core idea of the project is to combine detection and correlation, and the cell sequence samples are trained by a U-Net network model composed of 3D CNNs, which can track the migration, division, and entry and exit of cells in the field of view with high accuracy in all directions. The average detection accuracy of the cell coordinates is 98.38% and the average tracking accuracy is 98.70%. Highlights: Cell displacement, division, and entry and exit of cells in the field of view has been tracked. Our software is suitable for different types of cells. Bringing in the time axis and constructing a 3D convolutional neural network U-Net model. The average detection accuracy of the cells reached 98.38% and the average tracking accuracy reached 98.70%.